2021
DOI: 10.1177/10901981211000318
|View full text |Cite
|
Sign up to set email alerts
|

Protection Motivation During COVID-19: A Cross-Sectional Study of Family Health, Media, and Economic Influences

Abstract: Background Protection motivation to practice preventive behaviors is necessary for sustained mitigation during coronavirus disease 2019 (COVID-19); however, limited research exists on the ecological sources of influence for COVID-19 protection motivation. Aim To explore sources of influence (family health, media consumption, and loss of work hours) on COVID-19 protection motivation. Method An online quantitative survey of U.S. adults ( N = 501) aged 18 years or older was administered using Qualtrics with parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 60 publications
2
23
0
1
Order By: Relevance
“…It has been demonstrated that the Family Health Inventory has good reliability and validity. Cronbach’s α for this study ranged from .82 to .94, which is consistent with prior studies [ 31 ]. The Cronbach’s alpha of the Chinese version of the Family Health Scale was 0.83, and the Cronbach’s alpha of the subscales ranged from 0.70 to 0.90, indicating that the internal consistency of the scale was good.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that the Family Health Inventory has good reliability and validity. Cronbach’s α for this study ranged from .82 to .94, which is consistent with prior studies [ 31 ]. The Cronbach’s alpha of the Chinese version of the Family Health Scale was 0.83, and the Cronbach’s alpha of the subscales ranged from 0.70 to 0.90, indicating that the internal consistency of the scale was good.…”
Section: Discussionsupporting
confidence: 91%
“… 17 , 31 , 41 , 42 In the COVID-19 pandemic, researchers showed that PMT was a powerful tool in analyzing preventive behaviors. 12 , 43 , 44 These studies showed that evaluation of the risk of threat and the individual’s coping ability was closely related to protective behaviors. Some other studies explored the relationship between threat and coping appraisal and motivation for protective behaviors more nuancedly.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread circulation of COVID-19 in various countries has forced the world community to see the fact that the world is changing in various aspects of life. Changes in the social, economic, political, legal, and educational fields have forced people to change the meaning, the pattern of life, and daily life (Zuriah, 2021), (Hanson et al, 2021), (Wildman et al, 2021). The COVID-19 pandemic has impacted the world's first and major health crisis.…”
Section: Introductionmentioning
confidence: 99%